Typology of artisanal and small-scale gold mining sites along the Singingi River, Riau Province - Okalia, Deno; Iskandar; Mulyanto, Budi; Sudadi, Untung (Journal of Degraded and Mining Lands Management, 2025)
Artisanal and small-scale gold mining (ASGM) in the Singingi Watershed has precipitated a multifaceted transformation of the landscape, resulting in severe geomorphological, sedimentological, and hydrological alterations. This study leveraged an integrative quantitative descriptive framework and advanced spatial analysis to systematically delineate post-mining land typologies along a 51.25 km stretch of the watershed, using high-resolution remote sensing data and validation from 243 strategically distributed sample points. Eight distinct land typologies (A-H) were identified based on detailed assessments of topographic attributes, particle size distribution, pit depth, and tailing mound characteristics. Notably, typology H—characterized by a flat terrain (slope <8%), shallow pit depths and tailing mound heights (<2 m), and a predominance of fine-textured soils—emerged as the most amenable to passive reclamation and natural vegetation regeneration. Overlay analyses further demonstrated that Sungai Paku Village harbors the largest expanse of typology H (108.16 ha), underscoring its critical priority for reclamation interventions. These findings provide a robust, evidence-based foundation for the development of adaptive reclamation strategies, offering valuable insights for restoring ecological and physical functions in mining-impacted environments. The study underscores the importance of integrating multidisciplinary spatial data to inform sustainable land management practices in regions severely affected by ASGM activities and as a reference for the community for reclamation priorities based on land typology.